If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(b + -4b) = 8b + -1b Combine like terms: b + -4b = -3b -1(-3b) = 8b + -1b Remove parenthesis around (-3b) -1 * -3b = 8b + -1b Multiply -1 * -3 3b = 8b + -1b Combine like terms: 8b + -1b = 7b 3b = 7b Solving 3b = 7b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7b' to each side of the equation. 3b + -7b = 7b + -7b Combine like terms: 3b + -7b = -4b -4b = 7b + -7b Combine like terms: 7b + -7b = 0 -4b = 0 Divide each side by '-4'. b = 0 Simplifying b = 0
| 3x-1=-32 | | 2+3(4+1)= | | 16=r+20 | | 7m-34=6m-4(-7-8m) | | 3-9(8x+2)=4 | | (3x^2)x^5= | | 11x+70=-128 | | 4.7x+4.1x=-15.84 | | 3x-9y=21y | | 6.8x=11.5 | | 14x-4=18x-7 | | 7(6)+3-5(6)= | | -54=-15-3x | | 48+4y-20=17y-12-5y | | 2z-4-z=2 | | n-13=-33 | | -14x^2-49=0 | | 6x-7=8x+15 | | 3(0)+2(0)+7= | | -25=-9+x | | 56-11x=199 | | y=3x^2+10x | | 55-12x=139 | | .4w+.6=-3 | | b+16=24 | | Xy-9z=3 | | 8x+23=3x-7 | | 3(1)+2(1)+7= | | 5n+6(5+8n)=30-5n | | 5d-14+3=2d+2 | | 10=x+6+2x | | 43=r-7 |